Blockchain as the basis of the economy - Akhmetova, A.S.; Yeskerova, Z.A.; Spanova, B.K. (BUKETOV BUSINESS REVIEW, 2019)
In this review article the author explains the basics of blockchain technology and some of its key concepts. The purpose of this article is to give a brief description of the currently existing options for using the blockchain in the economy and the information technology industry. The article will be of interest to people who are always in search of a new one; here are four specific applications that highlight technology. The authors want to prove the fact that the «blockchain» is ready to be a good replacement for an already outdated banking system. The paper also describes the main technological aspects and principles of the blockchain, which allows us to evaluate the use cases presented. After all, throughout history you can see evidence of the ability to change the value of a business. Today’s Internet serves as a digital marketplace, a platform for economic activity and a repository of virtually all human knowledge. The authors describe the main stages of evaluating a potential idea regarding the main aspects of the blockchain. This helps to understand the need to develop a detailed model of the feasibility of a blockchain. The overarching theme is that an increasing number of daily transactions involving money, stocks, and valuable documents can begin to be transmitted through distributed network registers based on a chain of blocks with cryptographic protection and with a better level of detail. The central argument is based on the fact that the blockchain will raise the market for the provision of services by speeding up calculations and cleaning, including «smart contracts», data delivery and gradual disintermediation. We also cover possible threats to this development, especially issues of regulation and discussion of potential risks arising from this new technology.